School Culture: Values within School in Promoting Students Foreign Language Habit at School - Kholis, Nur (EDUKASI: Jurnal Pendidikan Islam, 2018)
As school culture has an important role in an educational reform (Jusaite-Harbison & Rex, 2010), investigating its elements in encouraging students achievement is essential. This study aimed at revealing school cultural values held by the school members as well as factors underlying their school cultural values behind their efforts in promoting students foreign language habit at school. In-depth interviews with school principals and teachers were conducted in collecting data of this study. In addition, the results of classroom observations completed the data obtained from interviews. The results show that the school members put high values in the role of foreign language mastery in preparing future generation with global perspective, good personality and independence. Finally, high global competitions, educational policy and society demands are some factors underlying their school cultural values which, in turn, motivate them to promote students foreign language habit at school.